2007
DOI: 10.1016/j.cub.2007.09.039
|View full text |Cite
|
Sign up to set email alerts
|

Role of Septin Cytoskeleton in Spine Morphogenesis and Dendrite Development in Neurons

Abstract: Septins are GTP-binding proteins that polymerize into heteromeric filaments and form microscopic bundles or ring structures in vitro and in vivo. Because of these properties and their ability to associate with membrane, F-actin, and microtubules, septins have been generally regarded as cytoskeletal components [1, 2]. Septins are known to play roles in cytokinesis, in membrane trafficking, and as structural scaffolds; however, their function in neurons is poorly understood. Many members of the septin family, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
269
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(285 citation statements)
references
References 35 publications
13
269
0
3
Order By: Relevance
“…In neurons, septin 11 forms heterooligomeric complexes with septin 7 and septin 5 (9,18). Nevertheless, the regional and developmental distribution of septin 11 in the brain and in hippocampal cultures is not identical to that of septin 7 or septin 5 (8). These results and other heterooligomerization studies show that septin 11 is not always associated with septin 7 and septin 5 (7,15,19).…”
mentioning
confidence: 56%
See 1 more Smart Citation
“…In neurons, septin 11 forms heterooligomeric complexes with septin 7 and septin 5 (9,18). Nevertheless, the regional and developmental distribution of septin 11 in the brain and in hippocampal cultures is not identical to that of septin 7 or septin 5 (8). These results and other heterooligomerization studies show that septin 11 is not always associated with septin 7 and septin 5 (7,15,19).…”
mentioning
confidence: 56%
“…Each septin gene is expressed in several spliced forms. Although most septins are highly expressed in the brain (6), only recently is their role in neuronal function (7)(8)(9) and in neuropathology (10 -14) is beginning to be addressed for some septins.…”
mentioning
confidence: 99%
“…As the morphology of the Golgi complex depends to a large extent on the integrity of the surrounding cytoskeletal elements (Bard and Malhotra, 2006;Egea et al, 2006;De Matteis and Luini, 2008), the observed disruption of the Golgi complex could be also a consequence of altered cytoskeletal organization upon kdPKD1 expression. Additionally, cytoskeletal rearrangements fundamentally influence the formation and maintenance of dendritic structures, including elongation and branching of dendrites or spine formation (Gauthier-Campbell et al, 2004;Kim et al, 2006;Hayashi et al, 2007;Tada et al, 2007;Zhang and Macara, 2008). Accordingly, direct or indirect cytoskeletal effects of PKD can also participate in the observed dendritic rearrangements in transfected neurons, especially when taking into account that high level of PKD activity was observed not only around the neuronal Golgi but also in the cytoplasm of dendrites and even in the dendritic spines.…”
Section: Discussionmentioning
confidence: 99%
“…The septins also serve as a diffusion barrier between the bud and mother cortex, which in turn is required for the asymmetric distribution of several proteins involved in mitotic exit and cell polarization [47,48]. Interestingly, a recent paper reported that the septins are localized at the bases of "budlike" dendritic spines in hippocampal neurons and are important for dendritic spine development [49]. This finding suggests that septins' role in morphogenesis may be conserved between fungi and animal cells.…”
Section: Cytoskeletal Polymersmentioning
confidence: 99%